نحو برنامج تدریبى مقترح لتدریب طلاب قسم المکتبات والمعلومات بکلیة الآداب جامعة الاسکندریة فى مقرر التدریب العملى - د. منى عبد العزیز عبد الغفار (المجلة الدولية لعلوم المكتبات والمعلومات)
The research is an exploratory study of the views of the students in theDepartment of Libraries and Information - Alexandria University, on the course ofthe field training, and try to benefit from the open source programs and thewebsites that simulate the information services that the students training in thelibraries, and thus introduce students to the techniques used in the globallibraries. To Competition for the labor market.The study also concluded that thepractical training course should be taught for at least two full years, the number ofhours of the course should be increased, and the practical training plan should bedrawn from a consultative group of its members Teaching the department, andscientific trips to visit major libraries such as the National Library, the CentralLibrary of Cairo University, the American University Library, providing a computerlab equipped with available open source library programs to train students. Thereis no gap between the theoretical study and the actual reality, with the need tohold meetings between the professor of material and students before the trainingperiod, where the clarification of the training plan and explain everything relatedto the practical training program, in addition to coordination with the large anddiverse libraries for the training of students during the summer period, And tofocus on teaching the technological materials for students in a practical way andbring them all new in the field of specialization.The study also showed that the percentage of male students in the librarydepartment reached 2.6%, while the proportion of females reached 97.4%, whichindicates that there is an unclear reason for the reluctance of male students tojoin the department, and 63.3% of students said that the duration of training is insufficient, as explained 60% of the students were satisfied with the practicaltraining program. The opinions of the students on the evaluation of thesupervisors varied as the experience and seriousness of the training supervisorcame in first place by 73.3%, followed by his good knowledge to distinguishbetween students and determine their level in the second place by 62%. It turnedout that the benefits of practical training for students is to develop the ability todevelop Dialogue reached 84.6%, followed by the ability to confront students by81.3%, while the last place came the training component of what was studied by63.3%, so the views of students differed on their knowledge of recentdevelopments in the specialty, where they came to knowledge of globaldatabases In the first place with 36.6%, followed by open source systems by16.6%, while the self-lending technology and the index available on-line in thelast two places by 6.6%.